Advancements in Seismic Performance Assessment: A Review of Material Influence on Structural Response and Failure Mechanisms - Sumaan Nazir; Preetpal Singh (PT. Radja Intercontinental Publishing, 2025)
Seismic resilience is a fundamental concern in structural engineering, necessitating comprehensive assessments of material-specific performance under earthquake-induced forces. This review paper synthesizes existing research on the seismic behavior of different construction materials, including concrete, steel, timber, and composites, to identify research gaps and areas for future advancements. While prior studies have extensively analyzed individual materials, a comparative, data-driven approach remains underexplored. This paper critically examines material properties influencing seismic response, including displacement, stress distribution, failure modes, and factors of safety. The findings highlight the necessity for advanced modeling techniques and hybrid material applications to optimize seismic resilience. By bridging existing knowledge gaps, this review contributes to the development of performance-based seismic design methodologies, facilitating enhanced structural safety and sustainability.